Soil health and dragon fruit cultivation: Assessing the impact on soil organic carbon - Guillen, Saskia (2023)
Soil organic carbon (SOC) plays a crucial role in soil quality and nutrient availability. Agricultural practices, such as tillage and crop rotations, can affect SOC levels. Pitahaya cultivation, a growing crop in dry tropical environments regions may affect soil quality due to weed management. This study aims to assess the relationship between alternative crop management and pitahaya species on SOC sequestration. Two plots, each for yellow (Selenicereus megalanthus) and red (Hylocereus Undatus) pitahaya, were established. Rice husks were used as a natural mulch to prevent weed growth as a new control alternative. Soil sampling was conducted at different depths (0-5, 5-10, 10-20, and 20-30 cm) and locations (below plant vs row) within the pitahaya plots. The study found at the 0-5 cm section presents the highest concentration of organic carbon at 2.01%, 1.77%, and 1.97% below plant in red, yellow, and row in yellow plantation respectively. In comparison with 1.26% in row red plantation, they are significant differences. The analysis of carbon accumulation showed variability in each of the locations from 0-30 cm. Without significant differences with 50.34, 49.40, and 47.95 (t ha-1) below the yellow plant, row, and below red plant respectively. In the whole soil profile with 38,10 t ha-1 the row of the red plant is significantly different. Likewise, the age of the plantation or crop plays another important role in soil organic carbon sequestration. Despite having the same management, soil type, climate, and irrigation, the significant effect in this study shows that the different age of the plantations (2 years) marks a significant difference between the two plantations. The roots of the older plantation extend their roots more horizontally and achieve more organic carbon sequestration in the rows compared to the younger plantation.